Crop Responses to Furrow Diking in North Carolina. Issue 1 (1st June 2014) - Foote, William; Nuti, Russell; Edmisten, Keith; Jordan, David; Wells, Randy; Fisher, Loren
Abstract : Furrow diking is the practice of installing earthen dams to form small basins between crop rows to reduce water runoff and improve water retention. Furrow‐diking equipment is operated shortly after planting and has been used extensively in the southern Great Plains. Research evaluating crop response to furrow diking is limited in North Carolina and other southeastern states. Experiments were conducted to determine cotton ( Gossypium hirsutum L.) and peanut ( Arachis hypogaea L.) yields following furrow diking in conventional and strip tillage systems. Corn ( Zea mays L.) response to furrow diking was determined only in conventional tillage systems. In the experiments where tillage was compared, variability in cotton and peanut response to tillage was observed, whereas diking did not affect yield of these crops. In separate experiments with conventional tillage only, peanut and corn yields were not affected by the diking treatment. However, in one experiment conducted at five sites in conventional tillage only, cotton yield increased by 7% when furrow diking was included. Although these results indicate that peanut and corn may be nonresponsive to furrow diking on coarse‐textured soils in the coastal plain of North Carolina, additional research is needed to make a concrete assessment of potential of furrow diking on these crops. While variability was noted when comparing experiments, cotton responded favorably to furrow diking.